Prevention of Staphylococcus epidermidis Endophthalmitis by Different Moxifloxacin Prophylaxis Routes - S. Yovel, Oren; Ben Eliahu, Shmuel; Kleinmann, Guy (Current Drug Delivery, 2016)
Background: To investigate postoperative endophthalmitis (POE) prevention by moxifloxacin prophylaxis. Methods: After crystalline lens removal and intraocular lens (IOL) implantation, 18 rabbit eyes were injected intracameral with different coagulase negative staphylococci (CNS) inoculums in order to determine the minimum inoculum required for a reproducible POE model. Another 28 similar eyes were divided into Group A, which was implanted with standard IOLs with intracameral injection of 100 μg/0.1 ml moxifloxacin, Group B implanted with moxifloxacin presoaked IOLs, Group C treated as Groups A and B, and Group D (control) implanted with standard IOLs only. At the end of surgery, all eyes were injected with the minimal inoculum that had developed POE, and treated with topical moxifloxacin for 24 hours. They were then evaluated using 3 different POE scores. Results: The minimum CNS concentration that developed reproducible POE was 5x105 CFUs/0.1 ml. Scores: 1. Clinical endophthalmitis was judged in 5/7 (71%), 4/7 (57%), 2/7 (28%) and 7/7 (100%) of Groups A-D eyes, respectively, p=0.005 and 0.057 for Groups B and C compared to D, respectively. 2. Endophthalmitis Scores for Groups A-D were 14.5±6.8, 10.6±4.5, 12.0±3.9 and 18.6±1.7, respectively, p=0.015, and 0.07 for Groups B and C compared to D, respectively. 3. Hypoyon was noted in 2/6 (33%), 2/7 (28%), 2/7 and 6/7 (86%) of the Group A-D eyes, respectively, p=0.053, 0.03 and 0.03 for Groups A-C compared to D, respectively. Conclusion: POE can be best prevented by prophylactic moxifloxacin by presoaked IOLs treatment.
Keywords: Antibiotic prophylaxis